1993
DOI: 10.1029/92jd02394
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpene emissions from Scots pine and Norwegian spruce

Abstract: Rates of monoterpene emissions from Scots pine (Pinus sylvestris) and Norwegian spruce (Picea abies) have been measured at four sites in Sweden with a dynamic flow chamber technique. Forest floor emissions have been made in the pine forest with the static chamber technique. Sampling was done with Tenax TA and analysis and detection by GC and ion trap detection. The compounds A 3-carene and a-pinene were the predominant terpenes emitted from the crown and floor of the Scots pine forest. Alpha-pinene was the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
166
2
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(187 citation statements)
references
References 34 publications
18
166
2
1
Order By: Relevance
“…Emissions from ecosystems in these regions are often observed to be largely based on temperature-controlled evaporation from storage pools and independent of light [ Lerdau et al, 1997] with monoterpenes often observed accumulating within the forest atmosphere at night [Janson, 1993;Rinne et al, 2000;Bouvier-Brown et al, 2009]. However, monoterpene emissions from tropical ecosystems are generally assumed as emitted from de novo production in a light-dependent manner, analogous to isoprene .…”
Section: Light-dependent Leaf Level Emissionsmentioning
confidence: 99%
“…Emissions from ecosystems in these regions are often observed to be largely based on temperature-controlled evaporation from storage pools and independent of light [ Lerdau et al, 1997] with monoterpenes often observed accumulating within the forest atmosphere at night [Janson, 1993;Rinne et al, 2000;Bouvier-Brown et al, 2009]. However, monoterpene emissions from tropical ecosystems are generally assumed as emitted from de novo production in a light-dependent manner, analogous to isoprene .…”
Section: Light-dependent Leaf Level Emissionsmentioning
confidence: 99%
“…Some researches have claimed that relative humidity influences monoterpene emissions [e.g. Dement et al, 1975], whereas others have disputed it [Juuti et al, 1990;Janson, 1993]. The current monoterpene emission model does not include such dependencies [Guenther et al, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…However, the maximum flux (373 μg m -2 h -1 ) measured by Hellén et al (2006) with adsorbent tubes was notably higher than that quantified with the same technique in this study. Hellén et al (2006) assumed that needle litter and fine roots in topsoil were the main sources of the terpenoids, which were also suggested by the studies of Janson (1993) and Hayward et al (2001). The forest floor remained a source of terpenoids not only during the growing season, but also during winter, however, the flux level was clearly lowered, approximately by a factor of ten.…”
Section: Role Of the Boreal Forest Floor As A Voc Sourcementioning
confidence: 85%
“…Some field studies indicate that the majority of them may originate from decomposing organic matter and living plant roots (Janson 1993, Hayward et al 2001, Asensio et al 2008a, Leff and Fierer 2008, Gray et al 2010, Greenberg et al 2012. Soil microbial activity is correlated with net rates of VOC emissions over a range of different forest soils (Asensio et al 2007a, 2008b, Leff and Fierer 2008, which stresses the importance of microbes and microbial processes as sources of soil VOCs.…”
Section: Current Knowledge Of Forest Floor and Soil Voc Production Anmentioning
confidence: 99%
See 1 more Smart Citation